Institutional Barriers to Women Contesting for Political Positions, A Case of Iringa Municipality in Tanzania - , Christopher Mbunda; , Frank Phillipo; , Agnes Nzali (Archives of Current Research International, 2023)
The study was conducted to find out the barriers to women contesting for political positions. This study aimed to investigate the institutional barriers to women contesting for political positions in Iringa Municipality, Iringa region, Tanzania. The study adopted a cross sectional study design where interviews and Focus Group Discussions (FGDs) and document analysis were used to collect information from the women political leaders facing the barriers to contesting for political positions, Women Ex Members of parliament and the ward councillors. The thematic analysis was used to analyse qualitative information collected from the respondents. From the study findings, it is concluded that the institutional barriers that women encounter when contesting for political positions are Political parties, Political motivation, Supportive Networks, International Organizations, Governmental and Electoral Institutional policy and Religious Institutions. Therefore, the study recommended that in order to increase women political participation, political parties, supportive networks, international organisations, governmental and electoral institutional policy and the religious institutions are advised to pursue measures like taking advantage of the ongoing constitutional review process, the government should make sure that gender-equitable principles are incorporated into the new constitution in accordance with the nation's obligations under international, regional, and domestic agreements like the Beijing Platform for Action, the African Union's Agenda 2063, and the Convention on the Elimination of All Forms of Discrimination against Women, also by insisting formation of the intra party leadership quota trainings and mentoring between experienced and inexperienced women to improve leadership and decision-making, public speaking and self-assertion again is political campaigning to increase women’s political knowledge, skills and capacity without forgetting a general consideration on laws of campaigning funds that can promote or diminish women political participation.